Atividade anti-micobacteriana de extratos de folhas de Byrsonima crassa Nied - Leite, C. Q F [UNESP]; Sato, D. N.; Higuchi, C. T. [UNESP]; Sannomiya, M. [UNESP]; Pavan, F. R. [UNESP]; Vilegas, Wagner [UNESP] (My University, 2008)
In this study, the antimycobacterial activity of chloroformic and methanolic extracts obtained from Byrsonima crassa leaves was evaluated. Antimycobacterial activity was assessed through the microtechnique named Microplate Alamar Blue Assay (MABA) and the promising active principles were identified by spectrophotometric analysis. The chloroformic extract presenting 62.5 μg mL-1 minimum inhibitory concentration (MIC) showed to be active against tuberculosis bacillus. The MIC value of the methanolic extract was 1000 μg mL-1. For the chloroformic one , phytochemical analysis indicated that antimycobacterial activity might be related to the presence of triterpenes.
Antimycobacterial activity of Byrsonima crassa Nied leaf extracts
Keywords: Antimycobacterial activity; Byrsonima crassa; MABA; Malpighiaceae; Mycobacterium tuberculosis; alpha amyrenone; alpha amyrin; antimycobacterial agent; beta amyrin; isoniazid; lupeol; triterpene derivative; unclassified drug; antibacterial activity; assay; drug isolation; micromethod; microplate alamar blue assay; minimum inhibitory concentration; nonhuman; phytochemistry; plant leaf